El cuidado como amistad desde la Ética a Nicómaco - Symmes Avendaño, Bárbara Andrea (Veritas, 2025)
In this article, I seek to contribute to the development of the ethics of care from the perspective of Aristotelian virtue ethics. My analysis focuses on chapters VIII and IX of the Nicomachean Ethics. I propose that friendship offers a better framework for understanding care than philein, understood as a feeling of love, friendship, or affection (Curtzer, 2007, 221). The main thesis of the article is that care constitutes a new type of virtuous friendship not contemplated by Aristotle. In care, as in virtuous friendship, the other is valued as an end in themselves, which I consider an essential characteristic of virtuous friendship, implied in Aristotle’s definition of friendship as explicit mutual benevolence. I identify two main differences: first, while in virtuous friendship the moral good that unites friends is virtue, in care the moral good that unites them is the growth of one of them. The second difference lies in that moral access to the other, which in virtuous friendship occurs through shared virtuous activity, whereas in care, this access is achieved through empathy.